PERBANDINGAN KOMBINASI MODEL PEMBELAJARAN TIME TOKEN DAN PICTURE PUZZLE DENGAN TIME TOKEN DAN INDEX CARD MATCH - Yanti Kartina, Dwi; Hidayat, Saleh; Nizkon, Nizkon (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Education was a part of the learning process, the wrong learning process can cause studentsâ learning outcomes become less maximal, one effort in improving studentsâ learning outcomes was by using the model of learning. Examples are Time Token, Picture Puzzle and Index Card Match. The purpose of this study was to determine the comparison of student learning outcomes by using Time Token and Picture Puzzle learning models with Time Token and Index Card Match. The method in this research is Quasi Eksperimental method. Data collection techniques used in the form of giving a test of multiple choice questions. The result of this research is the learning model of time token model and Picture puzzle of the preliminary test score 31,72 and the final test is 88,78 and the t value in paired data t test is 34,69. While in the class of time token learning model and index card match has a preliminary test score of 20.28 and the final test of 81.40 and the value of t on the t test of pairwise data 46.69 while the t value in the t test of unpaired data is 4.11. So it can be concluded that there is comparison of learning outcomes between time token learning model and picture puzzle with time token and index card match.